Principles of Medical Assistance in Combat Heart Injury in Schemes and Algorithms - Sergii O. Siromakha; Polyna A. Danchenko (Ukrainian Journal of Cardiovascular Surgery, 2022)
Combat injury of the heart and main vessels currently remains a cornerstone in patients with polytrauma. According to the US Department of Defense Trauma Registry, the incidence of heart injuries as a component of chest injuries does not exceed 6%, however, mortality as high as up to 80% in this category of patients makes an impression.The recommendations developed at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine schematically reflect the basic principles of management of the patients with combat trauma at the 4th echelon of care. Schematic images include anatomical features of injuries of heart and main vessels, main radiological axes and views for the evaluation of cardiac structures, the principle of medical evacuation of patients with combat trauma, key emergency medical procedures provided at different echelons of care, classification of open and closed heart injuries, as well as the algorithm of planned and urgent diagnostic and therapeutic measures. Algorithms for the management of the wounded casualties were created by the specialists of the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine in conjunction with military trauma surgeons, based on their own experience in the management of combat trauma of the heart and main vessels (in the period of ATO/JFO, 2014-2022), standards of medical care in the context of NATO combat operations, as well as the Stanford Trauma Guidelines. Simplified but clear algorithms can be used as a guide for emergency care, as they clearly define the sequence of actions to avoid unnecessary diagnostic tests and save time in the treatment of life-threatening conditions.